(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract—Cylindrical components are important in several industrial applications. The surface quality plays a role in part performance. Non-ferrous surfaces are difficultto-finish due to several issues encountered in grinding that is optimum for ferrous metals. Burnishing process, as a metal deformation process, is believed to be more suitable since it eliminates sticking, wheel dulling and overheating. The main objective of this work is to optimize the burnishing process that can be used to finish the surface of machined parts. To achieve this, burnishing tool was designed and constructed in such a way that it can be simply mounted or fixed onto the tool holder of the CNC lathe machine. Experiments are made according to the response surface methodology (RSM), in order to improve the reliability of results and to reduce the size of the experimental plan without loss of accuracy. In this work, four burnishing parameters, namely, burnishing speed, feed, depth of penetration and number of passes were selected in order to study their effects on the surface roughness. Mathematical models, which depend basically on the utilized experimental design, have been developed. Variance of analysis was conducted to determine the prominent parameters and the adequacy of the models. The results showed that good surface roughness can be obtained with minimum cost by transferring the CNC lathe machine from machine tool to super-finishing machine using the proposed burnishing tool. From an initial average roughness of about Ra (4-5 µm), the specimen could be finished to average roughness of 0.09 µm.